Kajian Kesesuaian Lokasi Pengembangan Kawasan Pemakaman Umum di Kota Banjarbaru, Kalimantan Selatan - Wiyoga Triharto (Prodi Arsitektur Universitas Matana, 2021)
The need for burial land in the City of Banjarbaru is increasing along with the population growth every year. On the other hand, the availability of land for public cemeteries that does not increase is a problem. The way to overcome this problem is to develop a cemetery in a suitable new location. In achieving the objectives, the authors first collect and summarize primary and secondary data and conduct a literature review and applicable laws and regulations, followed by collecting data on the physical condition / environmental baseline. Second, determine the location of the public cemetery based on the land suitability score. The analysis on this target uses land suitability analysis using GIS. Third, analysis of population and mortality predictions. The analysis uses an analysis of the number of occupations and the size of the area. From the analysis, it is known that several new locations for burial development are still possible. Namely located in Sungai Tiung Village and Cempaka Village, Cempaka District and Gantung Manggis Village and East Landasan Ulin Village, Landasan Ulin District. Keywords : Banjarbaru City, Development of Public Cemeteries, Location Determination Analysis min.